Excluding ionospherically unsafe satellite geometries in GBAS CAT-I - Bria, Oscar N. (2017)
We show the results of the implementation of a preliminary algorithm for excluding ionospherically unsafe satellite geometries in Ground-Based Augmentation Systems Category I. Minimum knowledge of the ionospheric treat model is assumed and the assistance of the code-carrier divergence monitor is not considered. All the satellites in view above 5◦ in elevation are included in the computations. The inflation of the standard deviation of the vertical ionospheric gradient implements the exclusion. Full availability remains for a typical day in the site of La Plata Airport.